Mysticism and theology in Teresa de Jesús - Castro Sánchez, Secundino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
From her great religious experience and reflection, Teresa de Jesús behaves like a true theologian. This article highlights the process in wich she elaborates the systematization of her mystical experience around the person of Christ. Teresa supported her argumentation with theological methodology (in her own way). The article includes also the opinion of enlightened theologians. The justification of the mystical science depends on the theological presuppositions. Therefore, her conclusions are the result of her unique experience and her deep reflections on Christian faith and life.
Keywords: humanity of Christ; mysticism; contemplation; Spirit; Neoplatonism; Christology; biblical spirituality; dogmatic Theology; spiritual Theology